Kajian Literatur tentang Perkembangan Historis dan Transformasi Dakwah Gerakan Tarbiyah di Indonesia - Fuad, Ai Fatimah Nur (Jurnal Lektur Keagamaan, 2019)
This research analyses the historical development of the Tarbiyah movement in Indonesia. Specifically, it analyses on how and to what extent the da’wa of the Tarbiyah movement has been transformed due its changing of religious, social and political dynamics of Indonesia since 1970s until now. Based on this written document-based research, I argue that the gradual transition of the Tarbiyah movement from a politically repressed network of religious purists in the 1970-80s into a fully-fledged dakwah political party (the Prosperous Justice Party /PKS) was the outcome of new ‘political opportunities’ which emerged during a period of democratisation. The political situation during the time of the Tarbiyah movement’s emergence in the early 1980s saw state repression of Islamic movements and this constraint on political opportunity structures was one of the main factors causing the Liqo to be informally organised. Only in the post-New Order period (begun in 1998) did the movement start to generate its formal organizational structure in the shape of a political party named the PK(S). The move towards formality aimed to take advantage of the ‘political opportunity’ provided by a more democratic government, while the less formal and the informal aspects of their organisation supports the party in recruiting new members and mobilizing its sympathisers.Keywords: Da’wa, Tarbiyah movement, PKS, Politics, Indonesia.Penelitian ini mengkaji perkembangan historis gerakan Tarbiyah di Indonesia. Secara khusus, penelitian ini mengkaji mengenai bagaimana dan sejauhmana dakwah gerakan Tarbiyah ini telah mengalami transformasi disebabkan oleh perubahan dinamika keagamaan, sosial, dan politik Indonesia sejak tahun 1970-an sampai saat ini. Berdasarkan penelitian berbasis analisa dokumen tertulis untuk ini, saya berpendapat bahwa transisi bertahap gerakan Tarbiyah dari jaringan agama puritan yang ditekan secara politis pada tahun 1970-1980-an menjadi sebuah partai politik dakwah pada akhir 1990-an adalah hasil dari peluang politik atau ‘political opportunity' yang muncul selama periode demokratisasi. Situasi politik selama masa kemunculan gerakan Tarbiyah pada awal 1980-an menyebabkan represi negara atas gerakan Islam dan kendala pada struktur kesempatan politik ini adalah salah satu faktor utama yang menyebabkan liqo diorganisir secara informal. Pada periode pasca-Orde Baru (dimulai pada tahun 1998) gerakan ini mulai menghasilkan struktur organisasi formal dalam bentuk partai politik bernama PKS. Langkah perubahan menuju formalitas bertujuan untuk mengambil keuntungan dari 'peluang politik' yang dibuka oleh pemerintah yang lebih demokratis, sementara aspek yang kurang formal dan informal dari organisasi /gerakan mereka tetap bisa mendukung partai dalam merekrut anggota baru dan memobilisasi simpatisannya.Kata Kunci: Dakwah, Gerakan Tarbiyah, PKS, Politik, Indonesia.